2020
DOI: 10.3390/biomedicines8030059
|View full text |Cite
|
Sign up to set email alerts
|

Aptamers Increase Biocompatibility and Reduce the Toxicity of Magnetic Nanoparticles Used in Biomedicine

Abstract: Aptamer-based approaches are very promising tools in nanomedicine. These small single-stranded DNA or RNA molecules are often used for the effective delivery and increasing biocompatibility of various therapeutic agents. Recently, magnetic nanoparticles (MNPs) have begun to be successfully applied in various fields of biomedicine. The use of MNPs is limited by their potential toxicity, which depends on their biocompatibility. The functionalization of MNPs by ligands increases biocompatibility by changing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 97 publications
0
29
0
Order By: Relevance
“…In vitro testing has shown a decrease in the functional activity of blood phagocytes when exposed to ferrihydrite nanoparticles that did not contact plasma proteins. In vivo testing of ferrihydrite nanoparticles was shown that the water sol has chronic toxicity since it leads to morphological changes in the organs, mainly the spleen, which is characterized by the accumulation of iron nanoparticles in the form of hemosiderin, which gives a positive Perls reaction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro testing has shown a decrease in the functional activity of blood phagocytes when exposed to ferrihydrite nanoparticles that did not contact plasma proteins. In vivo testing of ferrihydrite nanoparticles was shown that the water sol has chronic toxicity since it leads to morphological changes in the organs, mainly the spleen, which is characterized by the accumulation of iron nanoparticles in the form of hemosiderin, which gives a positive Perls reaction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many aptamers are currently under investigations in clinical trials for the treatment of several diseases [ 28 , 29 ]. Aptamers increase biocompatibility and reduce the toxicity of magnetic nanoparticles used in biomedicine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of MNPs throughout the body is represented in Figure 5. It is important to note that with uncoated MNPs, a decrease in the size of the particles typically leads to an increase in concentration, resulting in a longer blood circulation time [104]. The most important safety mechanism to be investigated is interference of normal, physiologic iron metabolism after in vivo MNP degradation, as superfluous accumulation of intracellular iron may damage cellular components including nucleic acids and proteins [46].…”
Section: Toxicity Mechanismsmentioning
confidence: 99%